Strategi Penjualan Modem Router PT Solusi Media Semesta Periode 2022-2023 - Pranaramadhana, Chaerulifan; Suwanda, Siti Nuraisyah (Journal of Emerging Business Management and Entrepreneurship Studies, 2022)
PT Solusi Media Semesta is a data center service provider company. The product offered is a router modem. In this study, the research method used was an interview and document study; in the interview, the number of samples taken was two samples, namely the marketing manager of PT Solusi Media Semesta and one client from the company, namely PT ATMi. In this study, researchers tried to examine the sales strategy to increase the sales of modem routers at PT Solusi Media Semesta is engaged in the field of information technology. This study aims to overcome the sale of modem router PT Solusi Media Semesta to increase and not depend on only a few companies by creating a sales strategy to increase sales of router modems.